A high-performance polyhydroxyalkanoate and its preparation method and application
By using continuous reaction extrusion method and polyol chain extender in PHA materials, the insufficient performance of PHA materials in the processing and forming process is solved, and the preparation of high-performance polyhydroxy fatty acid ester is realized, which improves its thermal stability, processing performance and mechanical properties.
Patent Information
- Application Number
- CN202011157757.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-26
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-10-26
AI Technical Summary
During the processing and forming process, polyhydroxy fatty acid ester (PHA) materials have problems such as low melt strength, poor processing performance, weak mechanical properties and easy secondary crystallization, which affects their application performance.
The PHA is modified by continuous reaction extrusion method, and the processability and mechanical properties of the polyester are improved by adding polyol as a chain extender and melting reaction extrusion under the action of a high-efficiency esterification catalyst.
It significantly reduces the melt index of high-performance polyhydroxy fatty acid ester, improves its thermal stability and processing properties, and improves the mechanical properties of film materials, including elongation of fracture and strength of fracture.
Smart Images

Figure CN114479021B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomaterials, and in particular relates to a high-performance polyhydroxyalkanoate, a preparation method thereof and an application thereof. Background Art
[0002] Commonly used biopolymer materials include polylactic acid (PLA), polycaprolactone (PCL), polyhydroxyalkanoates (PHA), copolymers of butylene adipate and butylene terephthalate (PBAT), etc. The polymer materials formed by converting renewable raw materials into biomonomers through biological or chemical reactions and then further polymerizing them belong to fully biomaterials. After the fully biodegradable materials are used, they are composted or otherwise degraded, and the plastics are eventually converted into water and carbon dioxide by microorganisms, which is beneficial to environmental protection and in line with the direction of sustainable development. As a fully biodegradable material, PHA is different from other synthetic polyesters (polymerized in high-temperature reactors). PHA is prepared by microbial fermentation in an aqueous solution at room temperature, and is made through fermentation, precipitation, filtration, washing, centrifugal drying and other steps.
[0003] Since PHA can be produced by bacterial fermentation of corn slurry powder and sodium chloride, it is expected to achieve low-cost production of PHA by subsequent optimization of process conditions, which has certain competitive potential compared with non-renewable petroleum-based plastics. At the same time, PHA can be completely decomposed by microorganisms in the soil during use, and has broad application prospects in the field of agricultural mulch (Brandi H et al. Degradation and applications of polyhydroxyalkanoates. Can. J. Microbiol, 1995, 41: 143-153; Ong SY et al. Degradation of polyhydroxyalkanoate (PHA): review. 2017; Bugnicourt E et al. Polyhydroxyalkanoate (PHA): Review of synthesis, characteristics, preparation and potential applications in packaging. 2014). Compared with traditional mulch, it can effectively solve the problem of the difficulty of recycling existing non-degradable polyethylene (PE) mulch, which causes environmental pollution. However, compared with traditional polyester materials, PHA materials are prepared in a different way. Due to the different chemical structure and the lack of high-temperature melt chain extension processes in the reactor of traditional polyesters, the melt strength of the prepared polymers is often low, and the film processing performance is poor. They usually have weak mechanical properties, low crystallinity, long crystallization cycle, and easy secondary crystallization. In addition, during the processing and molding process, the ester bond breaks due to high temperature and screw shearing, resulting in thermal degradation, which further affects the mechanical properties of the molded material (Wang S et al. Modification and potential application of short-chain-length polyhydroxyalkanoate (SCL-PHA). Polymers 2016; 8: 273). Summary of the invention
[0004] To solve the above problems, the present invention adopts a continuous reaction extrusion method to modify PHA (polyhydroxyalkanoate), and under the action of an efficient esterification catalyst, polyols are added to extend the PHA chain to improve the processing performance and mechanical properties of polyester.
[0005] One of the purposes of the present invention is to provide a high-performance polyhydroxyalkanoate, comprising a copolyester segment of a polyhydroxyalkanoate segment and a first chain extender, wherein the first chain extender is selected from polyols.
[0006] In the above-mentioned high-performance polyhydroxyalkanoate, the first chain extender is selected from aliphatic polyols, preferably aliphatic diols having 2 to 10 carbon atoms, and more preferably at least one selected from ethylene glycol, propylene glycol, butanediol, and pentanediol;
[0007] The polyhydroxyalkanoate has a structure shown in molecular formula (I):
[0008]
[0009] Wherein, R is an alkyl group with a carbon chain length of 1 to 15,
[0010] The polyhydroxyalkanoate is selected from homopolymers or copolymers of hydroxyalkanoates having 4 to 18 carbon atoms, preferably selected from at least one of poly(3-hydroxybutyrate), poly(3-hydroxybutyrate-co-4-hydroxybutyrate), poly(3-hydroxybutyrate-co-3-hydroxyvalerate), and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate); the weight average molecular weight of the polyhydroxyalkanoate is M w Greater than or equal to 50000 g / mol, preferably M w Greater than or equal to 100,000 g / mol.
[0011] In the high-performance polyhydroxyalkanoate, based on 100 parts by mass of the polyhydroxyalkanoate, the amount of the first chain extender is 0.05 to 10 parts, preferably 0.1 to 5 parts.
[0012] The second object of the present invention is to provide a method for preparing the above-mentioned high-performance polyhydroxyalkanoate, comprising reacting components including the polyhydroxyalkanoate and a first chain extender to obtain the high-performance polyhydroxyalkanoate, which specifically comprises the following steps:
[0013] Step 1. Premixing the first chain extender and the catalyst;
[0014] Step 2: melt-react and extrude the mixture obtained in step 1 with polyhydroxyalkanoate to obtain the high-performance polyhydroxyalkanoate.
[0015] In the above preparation method, based on 100 parts by mass of the polyhydroxyalkanoate, the amount of the first chain extender is 0.05 to 10 parts, preferably 0.1 to 5 parts; the amount of the catalyst is 0.001 to 0.2 parts, preferably 0.001 to 0.2 parts;
[0016] The extrusion temperature is 100-250°C, preferably 100-180°C;
[0017] The melt reaction extrusion is carried out in a twin-screw extruder, which can be a co-rotating or counter-rotating twin-screw, with a screw speed of 0 to 500 rpm, preferably 20 to 250 rpm. The twin-screw extruder used in the present invention includes but is not limited to: Micro 27 twin-screw extruder produced by Leistritz, Germany, which has the function of co-rotating / counter-rotating switchable; PolyLab, EuroLab and other models of co-rotating twin-screw extruders produced by Thermo Fisher Scientific, USA; ZSK 30 co-rotating parallel twin-screw extruder produced by Coperion, Germany, etc.;
[0018] The catalyst is selected from metal salts or oxides of Group IVB and Group IVA, preferably selected from at least one of titanate catalysts and metal alkoxides, more preferably selected from at least one of tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetrabutyl zirconate, ethylene glycol titanium, ethylene glycol antimony, and dibutyl tin dioctoate, and most preferably selected from at least one of tetrabutyl titanate, ethylene glycol titanium, and ethylene glycol antimony.
[0019] A third object of the present invention is to provide a high-performance polyhydroxyalkanoate film, comprising the high-performance polyhydroxyalkanoate or the high-performance polyhydroxyalkanoate prepared by the above-mentioned preparation method.
[0020] The high-performance polyhydroxyalkanoate film provided by the present invention contains, in addition to the high-performance polyhydroxyalkanoate, at least one of a composite polymer, a nucleating agent, a second chain extender and an opening agent.
[0021] In the above-mentioned high-performance polyhydroxyalkanoate film, based on the total amount of the high-performance polyhydroxyalkanoate and the compounded polymer as 100 parts by mass, the amount of the compounded polymer is 0 to 99 parts, the amount of the nucleating agent is 0.02 to 30 parts, the amount of the second chain extender is 0.01 to 6 parts, and the amount of the opening agent is 0.02 to 10 parts; preferably, the amount of the compounded polymer is 50 to 99 parts, the amount of the nucleating agent is 1 to 20 parts, the amount of the second chain extender is 0.05 to 2 parts, and the amount of the opening agent is 0.05 to 5 parts.
[0022] In the above-mentioned high-performance polyhydroxyalkanoate film, the compound polymer is selected from biodegradable polyester compounds, preferably selected from at least one of polylactic acid (PLA), poly(butylene adipate / terephthalate) (PBAT), poly(butylene succinate / terephthalate) (PBST), and poly(butylene succinate / adipate) (PBSA); the compound polymer in the present invention is not limited to the above-mentioned polymer types, and other commonly used biodegradable polyester compounds can also be selected;
[0023] The nucleating agent is selected from inorganic nucleating agents, preferably at least one selected from nanocrystalline cellulose, talc, silicon dioxide, and flaky calcium carbonate; the nucleating agent in the present invention is not limited to the above-mentioned compounds, and other commonly used nucleating agents in polymerization reactions can also be selected;
[0024] The second chain extender is selected from at least one of polycarbodiimide, epoxy glycol, toluene diisocyanate, and antimony trioxide;
[0025] The opening agent is selected from fatty acid amide compounds, preferably at least one selected from oleamide, erucamide, and stearamide.
[0026] The fourth object of the present invention is to provide a method for preparing the above-mentioned high-performance polyhydroxyalkanoate film, comprising mixing the components including the high-performance polyhydroxyalkanoate, the composite polymer, the nucleating agent, the second chain extender, and the opening agent to obtain the high-performance polyhydroxyalkanoate film, which specifically comprises the following steps:
[0027] The method comprises the following steps: mixing the high-performance polyhydroxyalkanoate and the compound polymer, adding a nucleating agent, a second chain extender and an opening agent, mixing, melting and reacting in a twin-screw extruder; adding the obtained reaction product to a single-screw extruder for melting, extrusion and film blowing, and obtaining the high-performance polyhydroxyalkanoate film after cooling.
[0028] In the above-mentioned preparation method of high-performance polyhydroxyalkanoate film, the extrusion temperature of the twin-screw extruder is 50-300°C, preferably 100-200°C; the screw speed of the twin-screw extruder is 0-500rpm, preferably 50-300rpm, more preferably 100-220rpm; the extrusion temperature of the single-screw extruder is 50-300°C, preferably 100-200°C; the screw speed of the single-screw extruder is 0-150rpm, preferably 10-100rpm.
[0029] The present invention uses a polyol chain extender to extend the polyhydroxyalkanoate chain. Under the action of an efficient esterification catalyst, the melt index of the high-performance polyhydroxyalkanoate after chain extension is significantly reduced through a twin-screw continuous extrusion reaction, and the high-performance polyhydroxyalkanoate has better thermal stability, processing performance and mechanical properties, and the mechanical properties of the film material prepared by the high-performance polyhydroxyalkanoate are also improved. According to some embodiments of the present invention, the thickness of the continuous reaction extrusion modified PHA film is less than 50μm, or even less than 25μm, the elongation at break is not less than 300%, or even higher than 400%, and the breaking strength is greater than 15MPa, which can reach more than 20MPa.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. After the polyol is used to extend the chain of polyhydroxyalkanoate, the melt index can be significantly reduced, so that it has excellent thermal stability and processing performance;
[0032] 2. The present invention uses modified high-performance polyhydroxyalkanoate as raw material, performs chain extension modification through a twin-screw continuous extrusion process, and then prepares a film material through single-screw film blowing, which has excellent mechanical properties;
[0033] 3. The preparation method provided by the present invention is simple and easy to implement, can be produced continuously, is green and environmentally friendly, and can be easily industrialized. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 shows the second heating curve of PHA powder before and after extrusion at different speeds and temperatures. Figure 1-A In the figure, curves a and b are the second heating curves of PHA obtained in Comparative Example 1 and Comparative Example 4, respectively. Figure 1-B Curves a and b in the middle are the second heating curves of high-performance polyhydroxyalkanoates (modified PHA) obtained at different rotation speeds in Example 2 and Example 1, respectively. Figure 1-C Curves a and b in the middle are the second heating curves of the modified PHA obtained in Example 3 and Example 1 at different temperatures, respectively;
[0035] Figure 2 is the elongation at break parallel to the stretching (MD) direction of the PHA film obtained in Examples 1 to 3 and Comparative Examples 1 to 6 after film blowing;
[0036] Figure 3 It is the breaking strength in MD direction of PHA film after blown film obtained in Examples 1 to 3 and Comparative Examples 1 to 6. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0038] The test instruments and test conditions used in the examples are as follows:
[0039] Melt index (MFR) determination method: according to ISO 1133 standard, using Lloyd Davenport MFI-10 / 230 melt indexer, barrel temperature 150 ° C, mass load 2.16 kg, die diameter 2.095 mm, length 8 mm, preheating time 4 minutes, automatic cutting every set time, take 5 times to calculate the average value, and express the measurement result in grams per 10 minutes (g / 10min).
[0040] Thermal performance analysis (DSC): The test was carried out on a Discovery series differential scanning calorimeter (DSC) produced by TAInstruments. The processing software was TAInstruments Trios version 3.1.5. The DSC instrument was equipped with a Refrigerated Cooling System 90 mechanical refrigeration accessory. The test atmosphere was 50mL / min of nitrogen, and the sample amount required for the test was 5-10mg. The test procedure was as follows: first stabilize the temperature at 40°C, then increase the temperature to 220°C at 10°C / min and keep it constant for 1min to remove the thermal history, then cool down to -50°C at 10°C / min and keep it constant for 1min, and then increase the temperature to 220°C at 10°C / min. Record the cooling process and the second heating process to study the thermal properties of the sample. Through the DSC test, the software can directly derive the crystallization temperature ("T c ”), melting temperature (“T m ”), glass transition (“T g ”), thermal enthalpy change (“H”), etc.
[0041] Film tensile test: According to ISO 527-3 standard, the test was carried out using Instron's 3344 material testing machine, and the processing software was Bluehill 2.31 version. The film was cut into Type 5 in the ISO 527-3 standard parallel to the stretching direction (MD) and perpendicular to the stretching direction (CD), and placed in the Bluepard BPS-100CB constant temperature and humidity chamber (temperature 23°C, relative humidity 50%) of Shanghai Yiheng Scientific Instrument Co., Ltd. for 24 hours. During the test, the initial clamp spacing was 75mm, the test tensile rate was 100mm / min, and each sample was tested at least 5 times, and the average value was taken.
[0042] [Example 1] Preparation of high performance polyhydroxyalkanoates
[0043] The catalyst tetraethyl titanate used in the present invention is selected from Shanghai Yuanye Co., Ltd., ethylene glycol is selected from Sinopharm, polyhydroxyalkanoate (PHA, M w 300000 g / mol) was selected from Tianjin Green Element Company.
[0044] In Example 1, the PolyLab HAAKE TMPHA was modified by Rheomex OSPTW16 co-rotating twin-screw extruder (screw diameter 16 mm, L / D = 40). 100 parts of PHA powder were pre-mixed with 0.01 parts of catalyst and 0.5 parts of ethylene glycol by mass, and plasticized, reacted and extruded. The feeding rate of the pre-mixed PHA was 3 kg / h.
[0045] The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to feed the material and is not heated. The temperatures of sections 2-11 of the extruder are 140℃, 140℃, 150℃, 150℃, 150℃, 150℃, 150℃, 150℃, 150℃, and 150℃, respectively, and the screw speed is set at 50rpm. The PHA mixture is fed to the first section of the twin-screw extruder using the loss-in-weight feeder of the extruder, and the feeding rate is 3kg / h. After stable operation, the pressure of the twin-screw extrusion is 20-30bar, and the torque is about 46%. The die equipped with the extruder has two circular outlets with a diameter of 4mm each. After the sample is extruded from the die, it passes through a water bath cooling tank and is cut into cylindrical particles with a length of about 5mm by a pelletizer. After vacuuming in a vacuum drying oven at 70℃ for 4 hours (h), it is collected and packaged for use.
[0046] [Example 2] Preparation of high performance polyhydroxyalkanoates
[0047] In Example 2, the effect of different screw speeds on the continuous reactive extrusion of PHA was investigated. PolyLab HAAKE from ThermoFisher Technology Company, USA, was selected. TM PHA was modified by a Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16 mm, L / D = 40). 100 parts of PHA powder were pre-mixed with 0.01 parts of catalyst and 0.5 parts of ethylene glycol by mass, and plasticized, reacted and extruded. The feed rate of the pre-mixed PHA was 3 kg / h. The screw speed was changed to 150 rpm, and other conditions were controlled to be the same as in Example 1.
[0048] [Example 3] Preparation of high performance polyhydroxyalkanoates
[0049] In Example 3, the continuous reaction extrusion effect of PHA was investigated at a higher main reaction extrusion temperature of 160°C. PolyLab HAAKE TMPHA was modified by Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16 mm, L / D = 40). 100 parts of PHA powder were pre-mixed with 0.01 parts of catalyst and 0.5 parts of ethylene glycol by mass, and plasticized, reacted and extruded. The feeding rate of the pre-mixed PHA was 3 kg / h. The main reaction temperature of the extruder was changed to 160 ° C, and the screw speed was 50 rpm.
[0050] The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to feed and cannot be heated. The temperatures of sections 2-11 of the extruder are 150℃, 150℃, 160℃, 160℃, 160℃, 160℃, 160℃, 160℃, 160℃, 160℃ and 160℃, respectively, and the screw speed is set at 50rpm. The PHA mixture is fed to the first section of the twin-screw extruder using the extruder's own loss-in-weight feeder, and the feeding rate is 3kg / h. After stable operation, the pressure of the twin-screw extrusion is 20-30bar, and the torque is about 36%. The die equipped with the extruder has two circular outlets with a diameter of 4mm each. After the sample is extruded from the die, it passes through a water bath cooling tank and is cut into cylindrical particles with a length of about 5mm by a pelletizer. After vacuuming in a vacuum drying oven at 70℃ for 4h, it is collected and packaged for use.
[0051] [Comparative Examples 1 to 3] Preparation of polyhydroxyalkanoates
[0052] Comparative Examples 1 to 3 investigated the situation where ethylene glycol and catalyst were not added, and PHA was extruded using a PolyLab HAAKETM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16 mm, L / D=40) from Thermo Fisher Scientific, Inc., USA. Among them, Comparative Examples 1 to 3 were prepared by adding only PHA powder to the twin screws without adding ethylene glycol and catalyst, and plasticizing, reacting, and extruding, and other conditions were controlled to be the same as those of the corresponding Examples 1 to 3. Among them, PHA powder that was not modified by the screw was selected as Comparative Example 4.
[0053] [Example 4] Melt index test
[0054] The PHA particles prepared in the above Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to a melt index test, and the measurement method was as described above. The melt index of the PHA particles prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested at a temperature of 150° C. and a mass of 2.16 kg. The measured melt indexes are shown in Table 1. Among them, Comparative Example 4 is a PHA powder without any extrusion modification reaction.
[0055] Table 1 Melt index of Examples 1 to 3 and Comparative Examples 1 to 4 at 150°C and 2.16 kg
[0056]
[0057] The melt index of comparative examples 1-4 is 0.25-0.47 g / 10 min, with little change. Comparing Examples 1-3 with Comparative Examples 1-4, after adding catalyst and ethylene glycol, the melt index of PHA is reduced to a certain extent, and the molecular weight is increased, indicating that the catalyst and ethylene glycol can significantly promote the chain extension of PHA and lead to a reduction in the melt index.
[0058] The rotation speed has a significant effect on the melt index. Compared with 150°C and 30rpm (Example 1), at 150°C and 100rpm (Example 2), when other conditions are the same, the melt index decreases significantly. It can be inferred from the melt index that the chain extension effect is better at this time. The temperature has a smaller effect. Similarly, compared with 150°C and 30rpm (Example 1), at 160°C and 30rpm (Example 3), the melt index does not change significantly.
[0059] [Example 5] Differential Scanning Calorimetry (DSC) Test
[0060] All the above particles, including Examples 1 to 3 and Comparative Examples 1 to 4, were subjected to differential scanning calorimetry (DSC) testing according to the above steps. The second melting temperature (T m ) Melting enthalpy (△H m ), glass transition temperature T g and recrystallization enthalpy △H c The values of are shown in Table 2.
[0061] Table 2 DSC results of Examples 1 to 3 and Comparative Examples 1 to 4
[0062]
[0063]
[0064] The second heating curves of high performance polyhydroxyalkanoates at different temperatures and rotation speeds are shown in Figure 1. Figure 1-A As shown in Figure 1, the melting curve of PHA (Comparative Example 1) that was only extruded without adding catalyst and chain extender has almost no change, indicating that the single extrusion reaction has little effect on the thermodynamic properties of PHA. Figure 1-B It can be found that when 100 rpm is compared with 30 rpm (Example 2 and Example 1), the melting peak of the high-performance polyhydroxyalkanoate obtained in Example 2 has no obvious change, the recrystallization peak shifts to the left and ΔH c The decrease indicates that the crystal structure has changed under high speed. Due to the shear enhancement at high speed, the crystal structure is destroyed and the crystallinity decreases. Figure 1-CIn the example 3, when compared with the example 1, at high temperature, the recrystallization enthalpy of the high-performance polyhydroxyalkanoate obtained in the example 3 is reduced and the crystallinity is decreased, indicating that high temperature is also not conducive to crystallization.
[0065] By comparing Comparative Examples 1 to 4 with Examples 1 to 3, after adding polyol chain extender and catalyst to PHA chain extension in the present invention, its crystallization melting enthalpy does not change significantly, while T g There is a certain reduction, which indicates that the polymer chain mobility of the material is enhanced.
[0066] [Comparative Examples 5-6]
[0067] In Comparative Examples 5 to 6, PHA was modified using monoalcohols
[0068] PolyLab HAAKE from Thermo Fisher Scientific, USA TM Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16 mm, L / D=40). 100 parts of PHA powder, 0.01 parts of catalyst and different amounts of n-butanol (Sinopharm) were pre-mixed by mass, plasticized, reacted and extruded, and the feeding rate of the pre-mixed PHA was 3 kg / h. Among them, the amount of n-butanol added in Comparative Example 5 was 0.1 parts, and the amount of n-butanol added in Comparative Example 6 was 1 part, and other conditions were controlled to be the same as those in Example 1.
[0069] [Example 6] Preparation of high performance PHA-PBAT film
[0070] All the above PHA particles, including Examples 1 to 3 and Comparative Examples 1 to 6, were prepared in the PolyLab HAAKE TM In a Rheomex OS PTW16 co-rotating twin-screw extruder (screw diameter 16 mm, L / D = 40), PBAT was melt-blended and modified to prepare PHA-PBAT blended particles. 10 parts by weight of high-performance polyhydroxyalkanoate was blended with 90 parts of PBAT (purchased from BASF, brand FBlendC1200), 0.5 parts of epoxy chain extender ADR (BASF), 0.5 parts of opening agent erucic acid amide (Jiangxi Zhilian Plastic Technology Co., Ltd.), and 5 parts of nucleating agent talc (Kain Chemical), and then plasticized, reacted, and extruded.
[0071] The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to feed and cannot be heated. The temperatures of sections 2-11 of the extruder are 140℃, 140℃, 150℃, 150℃, 150℃, 150℃, 150℃, 150℃, 150℃, 150℃ and 150℃, respectively, and the screw speed is set at 200rpm. The PHA mixture is fed to the first section of the twin-screw extruder using the loss-in-weight feeder of the extruder, and the feeding rate is 6kg / hr. After stable operation, the pressure of the twin-screw extruder is 20-30bar, and the torque is about 46%. The die equipped with the extruder has two circular outlets with a diameter of 4mm each. After the sample is extruded from the die, it passes through a water bath cooling tank and is cut into cylindrical particles with a length of about 5mm by a pelletizer. After vacuuming in a vacuum drying oven at 70℃ for 4 hours, it is collected and packaged for use.
[0072] All the above-mentioned PHA-PBAT blended particles, including Examples 1 to 3 and Comparative Examples 1 to 4, were blown into films on a HAAKETM Rheomex OS single-screw extruder manufactured by ThermoFisher Scientific Inc., USA. The screw diameter of the extruder was 19 mm, the aspect ratio was 25, and it was equipped with a 3:1 standard metering screw. The single-screw extruder was manufactured by HAAKETM PolyLab TM The extruder is controlled by OS torque rheometer platform. The extruder has four heating sections, numbered 1 to 4 from the feed port to the outlet, and is equipped with a blown film die with a heating function, a die diameter of 19.5mm, a die gap of 0.5mm, a screw speed of 50rpm, and the temperatures of each section are set to 50℃, 135℃, 145℃ and 145℃, respectively. The film is then made into a film through cooling, shaping, stretching and winding, and the thickness is controlled to be about 15μm.
[0073] [Example 7]
[0074] The films of all nine types of particles were subjected to tensile property tests parallel to the stretching direction (MD) according to the above steps. The results are shown in Figure 2 and Figure 3 .
[0075] exist Figure 2It can be seen that compared with the comparative example 4 which has not been modified in any way, the elongation at break of the film strip is 416%. The elongation at break of the corresponding film strips of comparative examples 1 to 3 is reduced to about 330% only by continuous reaction extrusion through reaction extrusion. However, after adding ethylene glycol and a catalyst to extend the PHA chain, the elongation at break of the corresponding film strips of Examples 1 to 3 of the present invention has increased significantly as a whole, to about 540%. It can be seen that after chain extension through polyol reaction extrusion, the mechanical elongation of the PHA film is significantly improved. Comparing the film strips corresponding to Example 1 with those of Comparative Examples 5 to 6, after modification with 0.1% monoalcohol (Comparative Example 5), the mechanical elongation of the PHA film has decreased from 416% to 337%, and after adding 1% monoalcohol (Comparative Example 6), the elongation has further decreased, indicating that the introduction of monoalcohol has reduced the elongation of the film strips, because after the addition of monoalcohol, an ester exchange reaction will occur, resulting in chain breakage, thereby reducing the elongation of the film. Figure 3 In the breaking strength, compared with the films containing comparative examples 1 to 3, the breaking strength of the films containing embodiments 2 and 3 with the addition of diols and catalysts is significantly improved, and is also better than the film containing comparative example 4 without any modification, indicating that after the continuous reaction extrusion chain extension of the polyol, the breaking strength of the modified high-performance PHA-PBAT film is significantly improved, and it also indicates that the continuous reaction extrusion can effectively improve the mechanical properties of the PHA-PBAT film.
Claims
1. A high-performance polyhydroxyalkanoate, comprising a polyhydroxyalkanoate segment and a copolyester segment of a first chain extender, wherein: The first chain extender is selected from aliphatic diols with carbon atoms of 2 to 10; the amount of the first chain extender is 0.1 to 0.5 parts based on 100 parts by mass of the polyhydroxyalkanoate; the polyhydroxyalkanoate is chain extended by the chain extender under the action of a catalyst, and the catalyst is selected from at least one of tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetrabutyl zirconate, ethylene glycol titanium, ethylene glycol antimony, and dibutyltin dioctoate; the chain extension is carried out in a twin-screw extruder at an extrusion temperature of 100 to 250°C.
2. The high performance polyhydroxyalkanoate according to claim 1, characterized in that: The polyhydroxyalkanoate has a structure shown in molecular formula (I): (I) Wherein, R is an alkyl group with a carbon chain length of 1 to 15.
3. The high performance polyhydroxyalkanoate according to claim 2, characterized in that: The polyhydroxyalkanoate is selected from homopolymers or copolymers of hydroxyalkanoic acids having 4 to 18 carbon atoms; and / or, The weight average molecular weight M of the polyhydroxyalkanoate w Greater than or equal to 50,000 g / mol.
4. The high performance polyhydroxyalkanoate according to claim 3, characterized in that: The weight average molecular weight M of the polyhydroxyalkanoate w Greater than or equal to 100,000 g / mol.
5. The high performance polyhydroxyalkanoate according to claim 3, characterized in that: The first chain extender is selected from at least one of ethylene glycol, propylene glycol, butanediol and pentanediol; and / or, The polyhydroxyalkanoate is selected from at least one of poly (3-hydroxybutyrate), poly 3-hydroxybutyrate-co-4-hydroxybutyrate), poly (3-hydroxybutyrate-co-3-hydroxyvalerate), and poly (3-hydroxybutyrate-co-3-hydroxyhexanoate).
6. A method for preparing the high-performance polyhydroxyalkanoate according to any one of claims 1 to 5, comprising reacting components including the polyhydroxyalkanoate and a first chain extender to obtain the high-performance polyhydroxyalkanoate.
7. The preparation method according to claim 6, characterized in that: The preparation method specifically comprises the following steps: Step 1. Premixing the first chain extender and the catalyst; Step 2. The obtained mixed solution is blended with 100 parts of polyhydroxyalkanoate and added to the twin-screw extruder together, or the mixed solution and polyhydroxyalkanoate are added to the extruder separately in the second stage through a syringe pump, and then mixed, melted, reactively grafted and extruded, and then cooled and granulated.
8. The preparation method according to claim 7, characterized in that: Based on 100 parts by mass of the polyhydroxyalkanoate, the amount of the first chain extender is 0.1 to 0.5 parts, and the amount of the catalyst is 0.001 to 1 parts; and / or, The extrusion temperature is 100-250°C; and / or, The melt reaction extrusion is carried out in a twin-screw extruder.
9. The preparation method according to claim 8, characterized in that: Based on 100 parts by mass of the polyhydroxyalkanoate, the amount of the catalyst is 0.001 to 0.2 parts; and / or, The extrusion temperature is 100-180°C; and / or, The screw speed of the twin-screw extruder is 5 to 1200 rpm; and / or, The catalyst is selected from at least one of tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetrabutyl zirconate, titanium glycolate, antimony glycolate and dibutyltin dioctoate.
10. The preparation method according to claim 9, characterized in that: The screw speed of the twin-screw extruder is 20-250 rpm; and / or, The catalyst is selected from at least one of tetrabutyl titanate, titanium glycolate and antimony glycolate.
11. A high-performance polyhydroxyalkanoate film, comprising the high-performance polyhydroxyalkanoate according to any one of claims 1 to 5 or the high-performance polyhydroxyalkanoate prepared by the preparation method according to any one of claims 6 to 10.
12. The film according to claim 11, characterized in that The film also contains at least one of a composite polymer, a nucleating agent, a second chain extender and an opening agent.
13. The film according to claim 12, characterized in that Based on the total amount of the high-performance polyhydroxyalkanoate and the compound polymer as 100 parts by mass, the amount of the compound polymer is 0 to 99 parts, the amount of the nucleating agent is 0.02 to 30 parts, the amount of the second chain extender is 0.01 to 6 parts, and the amount of the opening agent is 0.02 to 10 parts.
14. The film according to claim 13, characterized in that Based on the total amount of the high-performance polyhydroxyalkanoate and the compound polymer as 100 parts by mass, the amount of the compound polymer is 50-99 parts, the amount of the nucleating agent is 1-20 parts, the amount of the second chain extender is 0.05-2 parts, and the amount of the opening agent is 0.05-5 parts.
15. The film according to claim 14, characterized in that The compounded polymer is selected from biodegradable polyester compounds; and / or, The nucleating agent is selected from inorganic nucleating agents; and / or, The second chain extender is selected from at least one of polycarbodiimide, epoxy glycol, toluene diisocyanate, and antimony trioxide; and / or, The opening agent is selected from fatty acid amide compounds.
16. The film according to claim 15, characterized in that The composite polymer is selected from at least one of polylactic acid, poly(butylene adipate / butylene terephthalate), poly(butylene succinate / butylene terephthalate), and poly(butylene succinate / butylene adipate); and / or, The nucleating agent is selected from at least one of nanocrystalline cellulose, talcum powder, silicon dioxide, and flaky calcium carbonate; and / or, The opening agent is selected from at least one of oleamide, erucamide and stearamide.
17. A method for preparing the high-performance polyhydroxyalkanoate film according to any one of claims 11 to 16, comprising mixing the components including the high-performance polyhydroxyalkanoate, a composite polymer, a nucleating agent, a second chain extender, and an opening agent to obtain the high-performance polyhydroxyalkanoate film.
18. The preparation method according to claim 17, characterized in that: The preparation method specifically comprises the following steps: The method comprises the following steps: mixing the high-performance polyhydroxyalkanoate and the compound polymer, adding a nucleating agent, a second chain extender and an opening agent, mixing, melting and reacting in a twin-screw extruder; adding the obtained reaction product to a single-screw extruder for melting, extrusion and film blowing, and obtaining the high-performance polyhydroxyalkanoate film after cooling.
19. The preparation method according to claim 18, characterized in that: The extrusion temperature of the twin-screw extruder is 50-300° C.; and / or, The screw speed of the twin-screw extruder is 5 to 1200 rpm; and / or, The extrusion temperature of the single screw extruder is 50-300° C.; and / or, The screw speed of the single screw extruder is 5-150 rpm.
20. The preparation method according to claim 19, characterized in that: The extrusion temperature of the twin-screw extruder is 100-200° C.; and / or, The screw speed of the twin-screw extruder is 50-300 rpm; and / or, The extrusion temperature of the single screw extruder is 50-200° C.; and / or, The screw speed of the single screw extruder is 10-100 rpm.
21. The preparation method according to claim 20, characterized in that: The screw speed of the twin-screw extruder is 100-220 rpm.
Citation Information
Patent Citations
Multi-layer composite multifunctional fully biologically degradable plastic mulching film and preparation method thereof
CN109566210A